2019
DOI: 10.1016/j.jaad.2018.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psoriatic arthritis in patients with psoriasis: A systematic review and meta-analysis of observational and clinical studies

Abstract: We found that 1 in 4 patients with psoriasis have PsA. With the growing recognition of the Classification Criteria for Psoriatic Arthritis, more homogenous and comparable prevalence estimates are expected to be reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
247
1
25

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 432 publications
(322 citation statements)
references
References 271 publications
12
247
1
25
Order By: Relevance
“…A systematic review revealed 14.0%-22.7% of psoriasis patients having arthritis PsA in psoriasis patients [35]. PsA is characterized by enthesitis and arthritis in peripheral and axial involvement with bone proliferation and erosion [36,37].…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…A systematic review revealed 14.0%-22.7% of psoriasis patients having arthritis PsA in psoriasis patients [35]. PsA is characterized by enthesitis and arthritis in peripheral and axial involvement with bone proliferation and erosion [36,37].…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…Psoriatic arthritis (PsA) is part of the spondyloarthritis spectrum and affects 10–30% of people with psoriasis . Patients with PsA may have enthesitis, synovitis, and osteitis, in addition to variable skin involvement, resulting in a highly heterogeneous clinical presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 25% of patients with psoriasis also develop chronic inflammatory arthritis called psoriatic arthritis [99]. There is currently no method to predict the development of psoriatic arthritis in a patient with only psoriasis before symptoms appear.…”
Section: Psoriatic Arthritismentioning
confidence: 99%